2013
DOI: 10.1371/journal.pone.0059999
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders after Epilepsy Diagnosis: A Population-Based Retrospective Cohort Study

Abstract: BackgroundPsychiatric manifestations after occurrence of epilepsy have often been noted. However, the association between newly diagnosed epilepsy and psychiatric disorders afterward is not completely understood. We conducted two longitudinal cohorts for patients with and without epilepsy to investigate the risk factors and hazard ratios of developing psychiatric disorders after patients were newly diagnosed with epilepsy.MethodsWe identified 938 patients with a new diagnosis of epilepsy and 518,748 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
1
27
2
Order By: Relevance
“…11 Another study found that psychiatric disorders affect 41% patients with epilepsy. 3 The difference can be explained by the differences in study setting and sample size distribution. In our study attention deficit hyperactivity disorder (ADHD) was found in 5.8% of the respondents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Another study found that psychiatric disorders affect 41% patients with epilepsy. 3 The difference can be explained by the differences in study setting and sample size distribution. In our study attention deficit hyperactivity disorder (ADHD) was found in 5.8% of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other studies revealed that the common psychiatric co-morbidities found among patients with epilepsy were depression, neuroses (non-psychotic anxiety disorders) and psychoses. 3 It has been observed that 25%-40% of individuals with certain neurological conditions such as epilepsy will develop a marked depressive disturbance and psychotic symptoms at some point during the course of illness. 3 In our study, other co-morbidities included substance abuse, schizophrenia and social phobia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the bipolar disorder NOS presentation of our patient and data in the literature on links between epilepsy and bipolar disorder,24, 25, 26 we suggest there may be a link between resistant epileptic disease and bipolar disorder NOS in R(20). Therefore, we extrapolate that bipolar disorder features could be triggered or exacerbated by status epilepticus.…”
Section: Discussionmentioning
confidence: 63%